Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan pada PT. Karwikarya Wisman Graha Tanjungpinang - Misdiana Misdiana; Iranita Iranita; Roni Kurniawan (Bahtera Inovasi, 2018)
This study aims to determine the leadership style, work motivation and work environment towards employee job satisfaction at PT. Karwikarya Wisman Graha Tanjungpinang. The research method used is descriptive statistical method with a quantitative approach. Data collection techniques are carried out by observation and questionnaire. The number of research samples used was 115 respondents. Analysis of the data used is multiple linear regression analysis, hypothesis testing in the form of T test and F test and analysis of the coefficient of determination. The research conducted resulted in a leadership style that had a significant effect on employee satisfaction at PT. Karwikarya Graha Tanjungpinang because the value of t count> t table or 3.171> 1.981 and the significance value produced is 0.002 <0.05. Work motivation has a significant effect on employee satisfaction at PT. Karwikarya Graha Tanjungpinang because the value of t count> t table or 2,366> 1,981 and the significance value produced is 0.020 <0.05. The work environment has a significant effect on employee satisfaction at PT. Karwikarya Graha Tanjungpinang because the value of t count> t table or 7.168> 1.981 and the significance value produced is 0,000 <0.05.